2022
DOI: 10.1186/s12864-022-08365-3
|View full text |Cite
|
Sign up to set email alerts
|

Systematic benchmark of state-of-the-art variant calling pipelines identifies major factors affecting accuracy of coding sequence variant discovery

Abstract: Background Accurate variant detection in the coding regions of the human genome is a key requirement for molecular diagnostics of Mendelian disorders. Efficiency of variant discovery from next-generation sequencing (NGS) data depends on multiple factors, including reproducible coverage biases of NGS methods and the performance of read alignment and variant calling software. Although variant caller benchmarks are published constantly, no previous publications have leveraged the full extent of av… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 45 publications
4
39
0
Order By: Relevance
“…The hap.py [ 24 ] tool was used for benchmarking, which is a reference implementation of the GA4GH recommendations for variant caller benchmarking with the “vcfeval” engine for comparison; it generated metrics as “False positive”, “False negative”, “True positive”, “Precision”, “Recall”, and “F1 score”. It was found that three metrics are the most important for variant caller performance evaluations, which are “Precision”, “Recall”, and, most importantly, “F1 score”, which is the mean of precision and recall and is commonly used to test the performance of the callers [ 56 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hap.py [ 24 ] tool was used for benchmarking, which is a reference implementation of the GA4GH recommendations for variant caller benchmarking with the “vcfeval” engine for comparison; it generated metrics as “False positive”, “False negative”, “True positive”, “Precision”, “Recall”, and “F1 score”. It was found that three metrics are the most important for variant caller performance evaluations, which are “Precision”, “Recall”, and, most importantly, “F1 score”, which is the mean of precision and recall and is commonly used to test the performance of the callers [ 56 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another benefit of MinION over second-generation sequencers is its mobility and ease of use for library preparation and sequencing, as well as its low cost. There are currently many custom/academic or commercial BRCA1/2 target panels that have been established in recent years because of investigations on the use and impact of NGS in breast/ovarian cancer [ 56 , 60 , 61 , 62 ], the majority of which are based on the amplicon sequencing technique. There are currently many commercial short-read amplicon-based BRCA gene panels available that detect SNV and/or copy number variation.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the actual potential reduction in false positives, an estimation can be provided based on recent studies where multiple variant callers are evaluated ( Barbitoff et al., 2022 ; Lin et al., 2018 ) and combined ( Zhao et al., 2020 ). In ( Zhao et al., 2020 ), the authors benchmarked GATK, the Illumina DRAGEN-based caller and DeepVariant using human genome data and it was shown that the average F1-score for SNP detection across 4 datasets is 0.990 for GATK without Variant Quality Score Recalibration and 0.969 for GATK with Variant Quality Score Recalibration.…”
Section: Expected Outcomesmentioning
confidence: 99%
“…In addition, in ( Lin et al., 2018 ), the comparison of GATK with DeepVariant, when applied on the analysis of trios, showed that DeepVariant made fewer calls, but with a lower false positive rate. In addition, in ( Barbitoff et al., 2022 ), the F1-scores calculated for the three methods when applied on Whole Exome Sequencing were 0.996 for DeepVariant, 0.985 for GATK and 0.987 for FreeBayes. Based on these results and the aforementioned results regarding algorithm combination, we expect the overall F1-score to be >0.996.…”
Section: Expected Outcomesmentioning
confidence: 99%
“…In concert with the recent advances in high-throughput sequencing technology, many software tools have been developed for the computational processing of genomic sequencing data, each with their own distinct errors and biases. In fact, systematic comparisons of computational pipelines across multiple high-throughput sequencing platforms indicated high divergence and low concordance among the identified variants (O’Rawe et al 2013 ; Pirooznia et al 2014 ; Hwang et al 2015 ; Chen et al 2019 ; Kumaran et al 2019 ; Krishnan et al 2021 ; Barbitoff et al 2022 ). Such differences in performance are particularly problematic for the identification of spontaneous (de novo) mutations as well as rare variants, with differences in pipeline design leading to several-fold variation in estimated mutation rates (Pfeifer 2021 ; Bergeron et al 2022 ) as well as high rates of missed variants (Peng et al 2013 ).…”
Section: Introductionmentioning
confidence: 99%